Aplikasi Remote Sensing dan Geographic Information System Untuk Monitoring Perubahan Penggunaan Lahan Dalam Menunjang LP2B Di Subak Intaran Barat, Kota Denpasar - SISKA MAILASARI; NI MADE TRIGUNASIH; INDAYATI LANYA (Agrotrop : Journal on Agriculture Science, 2022)
Remote Sensing and Geographic Information System Aplication For Monitoring Land Use Change In Supporting LP2B In Subak Intaran Barat, Denpasar City. Subak Intaran Barat is one of 41 subak in Denpasar City which has been designated as Sustainable Subak and agro-ecotourism and is recommended as a Sustainable Food Agricultural Land area. This study aims to create a thematic map of changes in paddy land use in 2012 and 2018, a map of paddy land ownership, and compile an information system of Land Resources (SDL), Artificial Resources (SDB), and Agricultural Resources (SDP). This research method, namely: analysis of satellite images, surveys and mapping. The stages of this research are: literature study, interpretation of satellite images, field surveys and interviews, reinterpretation of satellite images, mapping and compilation of attribute data for SDL, SDB, SDP, and land ownership. Changes in land use for 6 years (2012-2018) in the West Intaran subak covering an area of 8.9 acres. The number of Subak farmers is 76 people. The status of the owner is 6 people with a land area of 6.85 acres (8.00%) and 70 smallholders with a land area of 79.55 acres (92%) who come from Sanur Kauh Village. Land resources found in Subak Intaran Barat are: irrigation canals (5,120 m), jogging track (1,960 m), rainfall 1500-2000 mm/year, slope 0-2%, soil type Typic Tropaquepts Isohiptermic, rice crop rotation patterns, horticulture-rice.